2020
DOI: 10.22159/ajpcr.2020.v13i9.38655
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Toxicity-Induced by Nickel Oxide Nanoparticles Administration in Albino Rats During Gestation

Abstract: Objective: Despite the widespread of nickel oxide nanoparticles (NiO NPs) and their benefits in all fields, they have many negative effects on human life, especially expectant mothers and their fetus. The purpose of this study was to investigate the possible maternal and developmental toxicity-induced by NiO NPs administration during gestation. Methods: Three groups of pregnant rats were administered orally during days 5–19 of gestation, the pregnant rats were haphazardly designed into three groups (six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Increasing concern of the bio safety with respect to public health, AlNP can permeate biological barriers and accumulate in many organs as shown in several studies( Almeida et al, 2011 , Morsy et al, 2016b ), causing neurotoxicity both in vivo and in vitro ( Dong et al, 2011 , Chen et al, 2013 , Morsy et al, 2016a ), genotoxicity ( Balasubramanyam et al, 2009 ), in addition liver and kidney toxicity ( Morsy et al, 2016a ). Keelan, 2011 , Muoth et al, 2016 , Hamdi, 2020a , Hamdi, 2020b reported that NPs can penetrate the biological barriers, such as the blood–brain barrier (BBB), blood–testis barrier, and placental barrier. Zhang et al (2018) showed that Alumina nanoparticles caused neurodevelopmental toxicity in offspring of exposed female mice during pregnancy, and they indicated that the contents of aluminum were localized in the newborns hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing concern of the bio safety with respect to public health, AlNP can permeate biological barriers and accumulate in many organs as shown in several studies( Almeida et al, 2011 , Morsy et al, 2016b ), causing neurotoxicity both in vivo and in vitro ( Dong et al, 2011 , Chen et al, 2013 , Morsy et al, 2016a ), genotoxicity ( Balasubramanyam et al, 2009 ), in addition liver and kidney toxicity ( Morsy et al, 2016a ). Keelan, 2011 , Muoth et al, 2016 , Hamdi, 2020a , Hamdi, 2020b reported that NPs can penetrate the biological barriers, such as the blood–brain barrier (BBB), blood–testis barrier, and placental barrier. Zhang et al (2018) showed that Alumina nanoparticles caused neurodevelopmental toxicity in offspring of exposed female mice during pregnancy, and they indicated that the contents of aluminum were localized in the newborns hippocampus.…”
Section: Introductionmentioning
confidence: 99%